Dietary Supplementation With Hydroxyproline Enhances Growth Performance, Collagen Synthesis and Muscle Quality of Carassius auratus Triploid - Cao, Shenping; Xiao, Yangbo; Huang, Rong; Zhao, Dafang; Xu, Wenqian; Li, Shitao; Tang, Jianzhou; Qu, Fufa; Jin, Junyan; Xie, Shouqi; Liu, Zhen (Frontiers in Physiology, 2022)
An eight-week experiment was undertaken to examine the effect of dietary hydroxyproline (Hyp) supplementation on growth performance, collagen synthesis, muscle quality of an improved triploid crucian carp (Carassius auratus Triploid) (ITCC). Six isonitrogenous (340 g/kg diet), isolipidic (60 g/kg diet) and isocaloric (17.80 MJ/kg diet) diets were formulated containing a certain amount of Hyp: 0.09% (the control group), 0.39%, 0.76%, 1.14%, 1.53% and 1.90%. Each diet was randomly assigned to three tanks and each group was fed two times daily until apparent satiation. The results showed that growth performance and feed utilization of ITCC were significantly increased with the dietary Hyp level enhancing from 0.09 % to 0.76 %. Crude protein, threonine and arginine content in the dorsal muscle were substantially higher in fish given 0.76 % Hyp than fish fed the basal diet (P < 0.05). The muscle textural characteristics increased remarkably with the amount of Hyp in the diet rising from 0.09% to 1.53% (P < 0.05). Meanwhile, the contents of type I collagen (Col I) and Pyridinium crosslink (PYD) in the muscle of fish were significantly increased by dietary Hyp (P < 0.05). The muscle fiber diameter and density of the fish were significantly increased when fed with 0.76% Hyp (P < 0.05). Furthermore, dietary supplementation with an appropriate concentration of Hyp substantially increased the expression of genes involved in collagen synthesis (col1a1, col1a2, p4hα1, p4hβ, smad4, smad5, smad9, and tgf-β) and muscle growth (igf-1, tor, myod, myf5, and myhc) (P < 0.05). In conclusion, dietary supplementation of Hyp can enhance fish growth performance, collagen production, muscle textural characteristics and muscle growth of ITCC. According to the SGR broken-line analysis, the recommended supplementation level of Hyp was 0.74% in the diet for ITCC, corresponding to 2.2% of dietary protein.